2015
DOI: 10.3109/19396368.2014.1002139
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling of the human sperm associated antigen 11 B (SPAG11B) proteins

Abstract: Antimicrobial proteins and peptides are ubiquitous in nature with diverse structural and biological properties. Among them, the human beta-defensins are known to contribute to the innate immune response. Besides the defensins, a number of defensin-like proteins and peptides are expressed in many organ systems including the male reproductive system. Some of the protein isoforms encoded by the sperm associated antigen 11B (SPAG11) gene in humans are beta-defensin-like and exhibit structure dependent and salt tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Sperm-associated antigen families are the proteins that highly expressed in the testis and are essential for motile cilia and flagella [34]. Previous studies have indicated that alternative splicing of sperm-associated antigen genes play important roles in spermatogenesis [5,[35][36][37][38][39][40]. Three isoforms of human Spag11b including Spag11b-a, Spag11b-d and Spag11b-g were different in their 3D fold structure [35].…”
Section: Alternative Splicing Of Key Genes Involved In Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm-associated antigen families are the proteins that highly expressed in the testis and are essential for motile cilia and flagella [34]. Previous studies have indicated that alternative splicing of sperm-associated antigen genes play important roles in spermatogenesis [5,[35][36][37][38][39][40]. Three isoforms of human Spag11b including Spag11b-a, Spag11b-d and Spag11b-g were different in their 3D fold structure [35].…”
Section: Alternative Splicing Of Key Genes Involved In Spermatogenesismentioning
confidence: 99%
“…Previous studies have indicated that alternative splicing of sperm-associated antigen genes play important roles in spermatogenesis [5,[35][36][37][38][39][40]. Three isoforms of human Spag11b including Spag11b-a, Spag11b-d and Spag11b-g were different in their 3D fold structure [35]. Spag11b-d isoform could interact with tryptase alpha/beta 1 (Tpsab1), tetraspanin 7 (Tspan7), and attractin (Atrn), and then played major roles in immunity and fertility [36].…”
Section: Alternative Splicing Of Key Genes Involved In Spermatogenesismentioning
confidence: 99%